Prevalence and determinants of gambling disorder among older adults: A systematic review. (February 2015) - Subramaniam, Mythily; Wang, Peizhi; Soh, Pauline; Vaingankar, Janhavi Ajit; Chong, Siow Ann; Browning, Colette Joy; Thomas, Shane Andrew
Abstract: Aims: This paper aims to systematically review studies on the prevalence of gambling disorder among older adults aged 60 years and above and to summarize the evidence on the determinants, risk factors as well as the comorbidities associated with it. Methods: A systematic search was conducted for peer-reviewed, journal articles between 1st January 1995 and 1st May 2013. Only original studies which were published in English, included participants older than 60 years of age and provided prevalence figures specifically among them, and where participants were assessed to have a gambling disorder by a validated instrument in non-treatment seeking/non-clinical setting were included. Results: 25 eligible studies were identified from the literature. The prevalence of lifetime gambling disorder ranged from 0.01% to 10.6% across studies. Prevalence of gambling disorder is higher among the younger age groups (of older adults) and among males as compared to females. Those with gambling disorder were more likely to be single or divorced/separated. Findings indicate that older adults may gamble more in an effort to ameliorate negative emotional states; they may have limited access to other exciting activities or they may be unable to participate in activities that they were previously able to and they might attempt to fill this gap with gambling. Conclusions: Gambling disorder among older adults is a significant problem. Fixed incomes and limited prospects of future earnings make them an extremely vulnerable group. There is an urgent need to understand the phenomenon of gambling disorder in older adults. Highlights: Prevalence of lifetime problem or pathological gambling ranged from 0.01% to 10.9%. Gambling disorder among older adults is associated with significant comorbidity. Fixed incomes and limited future earnings render older adults a vulnerable group.